The association between dental caries and serum crp in the us adult population: evidence from NHANES 2015-2018 - Abdullah AlShammari; Saleh AlSaleh; Abdulaziz AlKandari; Sara AlSaqabi; Dalal AlJalahmah; Woroud AlSulimmani; Muath AlDosari; Hesham AlHazmi; Hend AlQaderi (BMC, 2024)
Abstract Background Dental caries remains one of the most prevalent diseases worldwide, affecting 29.4% of the global population. Despite numerous efforts to diagnose, predict, and prevent dental caries, the incidence continues to rise. Salivary biomarkers provide a non-invasive means for early detection of various oral conditions. C-reactive protein (CRP) is a key marker, elevated in both oral and general inflammatory conditions such as diabetes, periodontitis and oral squamous cell carcinoma. Considering the emerging connection between oral and systemic health, it is worth exploring the various factors associated with this widespread disease. This study investigates the association between CRP levels and dental caries in the United States population, utilizing data from the National Health and Nutrition Examination Survey (NHANES). Methods The study analyzed data from the 2015-2018 NHANES cycles, focusing on a nationally representative sample of individuals aged 30 years and above. Weighted multivariable negative binomial and logistic regression analyses were employed to explore the relationship between dental caries and CRP levels, adjusting for age, gender, race, education level, diabetes status, and gum disease. Results The results of the negative binomial regression analysis demonstrated a positive association between higher CRP levels and an increased mean number of dental caries (Adjusted Mean Ratio [AMR] = 1.7; 95% CI: 1.3 - 2; P: < 0.001). The logistic regression analysis showed that individuals with higher CRP levels have a 50% increase in the odds of developing dental caries (AOR: 1.5, CI: 1.2 - 1.9; P: < 0.01). Conclusion The results of this cross-sectional study of the U.S. population highlight the positive association between high CRP levels and increased dental caries. These findings contribute to the growing body of evidence supporting the integration of oral and systemic health care. Further research is necessary to deepen our understanding of the mechanistic relationship between CRP levels and dental caries.